1976
DOI: 10.1136/bmj.1.6009.547-a
|View full text |Cite
|
Sign up to set email alerts
|

Results of 250 consecutive cadaver kidney transplants.

Abstract: SummaryThe results of 250 cadaver kidney transplants performed at this hospital between May 1968 and December 1974 were analysed. A functioning transplant was defined strictly as one that maintained the recipient in good health with a serum creatinine below 442 pmol/l (5 mg/ 100 ml) without any need for dialysis. The proportions of kidneys functioning after one, two, and three years were 40 40, 33.9%, and 31 1% respectively, the corresponding survival rates of patients being 62 6%, 57*40°, and 43-8%.The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Marx experienced urological complications in only 3.5 per cent of patients (Man et al, 1974), although in a collective review of the experience of several centres this type of complication was reported in 14 per cent of renal transplant recipients (Weil et al, 1971). Renal artery occlusion has been reported after up to 8 per cent of allografts (Hall et al, 1976), but usually occurs in kidneys which are ischaemic and non-viable from the outset and should not be a problem in autotransplantation. Since urological complications are thought to be due, at least in part, to ureteral rejection and to immunosuppressive therapy, they too should be less frequent with autotransplants.…”
Section: Discussionmentioning
confidence: 96%
“…Marx experienced urological complications in only 3.5 per cent of patients (Man et al, 1974), although in a collective review of the experience of several centres this type of complication was reported in 14 per cent of renal transplant recipients (Weil et al, 1971). Renal artery occlusion has been reported after up to 8 per cent of allografts (Hall et al, 1976), but usually occurs in kidneys which are ischaemic and non-viable from the outset and should not be a problem in autotransplantation. Since urological complications are thought to be due, at least in part, to ureteral rejection and to immunosuppressive therapy, they too should be less frequent with autotransplants.…”
Section: Discussionmentioning
confidence: 96%